Production of ceramic pigments with diopside structure from TALC - Pogrebenkov V. M. (1998, 1998)
The results of investigation of synthesis of ceramic pigments with diopside structure are presented. Two reactions of diopside production are considered. It is indicated that the use of natural talc mineral makes it possible to lower the expense of pigment production and expand the pigment color range